Efeito de diferentes dietas no desempenho de pós-larvas Litopenaeus vannamei (Boone, 1931) em sistema de larvicultura com redução de 50% de artêmia. - Ramiro, Bianca de Oliveira (2020)
The production of brine shrimp does not always meet the demand of larvicultures due to its high cost, therefore, alternative diets need to be tested to compensate for this expense. Therefore, the objective of this work was to evaluate the effect of four diets with different formulations to test their efficiency with the partial replacement of brine shrimp (50% reduction) on the survival of Litopenaeus vannamei larvae. To carry out the experiment, commercial rations were distributed in 16 experimental units, being offered during the period of 18 days, which corresponds from hatching in nauplius to the harvest in pl 10. Four treatments were used: T1 (78% of crude protein (CP) + 50% reduction of artemia), T2 (70% of CP + 50% reduction of artemia), T3 (63% of CP + 50% reduction of artemia) and T4 (48% of CP) + 50% reduction of brine shrimp). The variables analyzed were Total number of larvae, Survival, Average weight of larvae, Sample of daily larvae, Larvae that would have survived, Total weight of larvae, Larvae biomass. The data obtained were subjected to analysis of variance and Tukey's post test for P <0.05, using the SAS statistical program. As a result, it was observed that the best values of larvae weight (0.41g), biomass (20.51g) and total number of larvae (5247) were found in the experimental units submitted to treatment 1. And the lowest values were in treatment 4 (39.10%); (0.23g); (14.16g) and (3909), respectively, greater survival was found in the experimental units submitted to treatment 1, corresponding to 52.47% and the lowest average in treatment 4, 39.10%. The water quality parameters did not differ between treatments. From the results, we can conclude that diets with compositions above 70% of marine proteins showed better results when compared to diets that do not have these compositions and protein levels. In this way, it is possible to reduce artemia by 50% of its consumption, since the rations supply the nutritional needs that the artemia offers, improving the survival and weight of the post-larvae, as well as the production cost.